2018
DOI: 10.1007/5584_2018_156
|View full text |Cite
|
Sign up to set email alerts
|

SERPINA1 Gene Variants in Granulomatosis with Polyangiitis

Abstract: Alpha-1 antitrypsin (A1AT) deficiency is one of the most common genetic disorders in Caucasian population. There is a link between granulomatosis with polyangiitis (GPA) and most frequent variants of SERPINA1 gene encoding severe alpha-1 antitripsin deficiency. However, the potential effect of Pi*Z, Pi*S as well as other SERPINA1 variants on clinical course of vasculitis are not well understood. The aim of the study was to analyze the potential effect of A1AT protein phenotype representing the SERPINA1 gene va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Individuals heterozygous for the Z allele exhibited higher FEV 1 (β = 9.26 ml, P = 0.041) but no association with FEV 1 /FVC or FVC compared to wild-type ( Table 2 ). However, in stratified analyses of UK Biobank never- and ever-smokers, we found that heterozygosity for the Z allele was associated with a large increase in FEV 1 (β = 19.36 ml, P = 9.21×10 - 4 ) and increased FEV 1 /FVC (β = 0.0031, P = 1.22×10 -5 ) in never-smokers, but not in ever-smokers (Table 2). Statistical tests of Z allele*ever-smoking interactions showed interactions for FEV 1 (P = 0.022) and FEV 1 /FVC (P = 1.06×10 -4 ) ( Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Individuals heterozygous for the Z allele exhibited higher FEV 1 (β = 9.26 ml, P = 0.041) but no association with FEV 1 /FVC or FVC compared to wild-type ( Table 2 ). However, in stratified analyses of UK Biobank never- and ever-smokers, we found that heterozygosity for the Z allele was associated with a large increase in FEV 1 (β = 19.36 ml, P = 9.21×10 - 4 ) and increased FEV 1 /FVC (β = 0.0031, P = 1.22×10 -5 ) in never-smokers, but not in ever-smokers (Table 2). Statistical tests of Z allele*ever-smoking interactions showed interactions for FEV 1 (P = 0.022) and FEV 1 /FVC (P = 1.06×10 -4 ) ( Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 83%
“…Some previous studies have sought to characterise the effect of Z allele heterozygosity and homozygosity on non-respiratory traits, particular liver diseases 2, 3, 4, 5, 6 . However, these have often been carried out in small sample sizes and/or clinical subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Several other genetic variants, not related to a specific treatment, have been associated with clinical outcomes of AAV. Examples include gene polymorphisms of monocyte chemoattractant protein-1 [73], alpha-1 antitrypsin [74], and human leukocyte antigen (HLA)-DPB1 [75].…”
Section: Other Genetic Associations With Outcomes Of Anca-associated Vasculitismentioning
confidence: 99%
“…Other responsible gene pathways include alpha-1 antitrypsin deficiency and polymorphisms of CTLA-4 (which is involved in T-cell activation) and Fcγ receptor IIIb on the surfaces of neutrophils and monocytes/macrophages. Furthermore, the presence of the PTPN22 R620W allele (associated with T-cell activation) and SERPINA1 gene variants has also been implicated in GPA [7, 8].…”
Section: Pathogenesismentioning
confidence: 99%